Forces into forms: a pragmatic sociology of “violentization” of force in different modalities - Werneck, Alexandre Vieira; Teixeira, Cesar Pinheiro; Caminhas, Diogo Alves; Talone, Vittorio da Gamma (SOCIOLOGIAS, 2024)
This article aims to discuss how force appears in moments of “violentization” in social situations, that is, when defining them as “violent,” when the horizon of this delimitation is under the social representation called “urban violence.” In order to do so, we analyzed, in a symmetrized way, in four empirical materials crossed by multiple methods, the effectuation of situations related to four different relevant figures of this scenario: 1) military police officers (that make themselves as force); 2) thieves (who manage force); 3) the so-called “bandits” (who are represented as force); and 4) readers of news about police military incursions in a newspaper (who summon the force). The work joins an effort to develop a pragmatic sociology of violence. It seeks to understand how types of force and ways of deploying them in a situation define different actants and, consequently, the situations they “violentize.”